Pengaruh Harga dan Kepercayaan terhadap Keputusan Pemesanan Kamar Menggunakan Online Travel Agent di Daima Hotel Padang : Studi Kasus Traveloka - Haris Ramadhan; Feri Ferdian (Jurnal Transformasi Bisnis Digital, 2024)
This analysis examines how price and trust influence the decision to book a room through online travel agencies in Daima Hotel Padang (Traveloka case study). with two independent variables consisting of price and trust, and the dependent variable consisting of the booking decision. This research is quantitative and uses a causal-associative approach. The sample consists of 194 respondents and a Likert scale was used for data collection. SEM-PLS 3 as data analysis. The hypotheses showed that ordering decision has no significant effect on price, with a t-statistic of 1.740 < 1.96 and a p-value of 0.083 > 0.05. On the other hand, ordering decision has a significant effect on trust, with a t-statistic of 5.922 > 1.96 and a p-value of 0.000 < 0.05.